The Discipline of Costume Composition is Inextricably Linked with Other Disciplines of the Educational Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Interesting facts have been written that the discipline of costume composition is inextricably linked with other disciplines of the educational process. Having an understanding of the silhouette of the suit, the main lines on the dress, the mass of the dress, I think it will help create very spectacular outfits in harmony with new styles.